MODEL SPEAKING DELL HYMES DALAM DIALOG INEWS “TIGA TERLAPOR IJAZAH JOKOWI BERSAKSI” - Winda Pramesti Naibaho; Dairi Sapta Rindu Simanjuntak; Natal Eliazer Girsang; Maretha Damai Simanjuntak (Universitas Islam Zainul Hasan Genggong, 2025)
This study aims to analyze verbal communication in the televised discussion “Tiga Terlapor Ijazah Jokowi Bersaksi” using Dell Hymes’ SPEAKING model within the framework of ethnography of communication. The research focuses on how communication elements—setting, participants, ends, act sequence, key, instrumentalities, norms, and genre—construct interaction dynamics in digital political discourse. A qualitative approach was applied, utilizing discourse analysis based on ethnographic communication. Data were collected from a live broadcast and transcribed dialogue, then systematically analyzed to uncover the structure and strategies employed by the participants. The findings show that the program serves not only as an informative space but also as a discursive arena for identity negotiation, ideological contestation, and representation of power. Each component of the SPEAKING model plays a significant role in shaping complex meanings in politically charged communication. The study concludes that the ethnographic communication approach is highly effective in examining speech acts within digital political contexts, revealing how verbal interactions are influenced by social positions, ethical considerations, and ideological interests.